First nests of Endangered Nordmann's Greenshank Tringa guttifer found in over 40 years indicate nesting plasticity. (23rd January 2023) - Maslovsky, Konstantin S.; Maleko, Philipp N.; Pronkevich, Vladimir V.; Slaght, Jonathan C.; Powell, Abby N.
Summary: Knowledge of the breeding ecology of Endangered Nordmann's Greenshank Tringa guttifer is necessary to develop a comprehensive species-specific conservation plan. We found nine greenshank nests in Schaste Bay, Russian Far East during the summers of 2019–2021. These are the first nests found in over 40 years and the only discovered to date on mainland Russia. In contrast to previous nest descriptions, we found greenshanks do not exclusively nest in trees, but also place nests on the ground at the base of mature or sapling larches. Our results indicate greenshanks may be larch obligates during the breeding season, and protecting coastal larch forest ecosystems near bogs, meadows, and mudflats throughout the Russian Far East may be critical to the species' conservation.